Fish tank - Ryan, Robbie 1970-; Jarvis, Katie 1991-; Fassbender, Michael 1977-; Wareing, Kierston 1978-; Treadaway, Harry 1984- (<<The>> Criterion collection, 2010)
British director Andrea Arnold won the Cannes Jury Prize for this searing and invigorating film about a fifteen-year-old girl, Mia, who lives with her mother and sister in the depressed housing projects of Essex. Mia's adolescent conflicts and emerging sexuality reach boiling points when her mother's new boyfriend enters the picture
Bildformat 1.33:1. - New, restored high-definition digital transfer
Orig.: Großbritannien, Niederlande 2009
Enth. new video interview with actor Kierston Wareing ; audio conversation with actor Michael Fassbender from 2009 ; audition footage ; stills gallery by set photographer Holly Horner